Modulation of Oxidative Stress Induced Cerebral Ischemia in Wistar Rats by Hydroalcoholic Extract of Talinum triangulare - Mathala, Nalini; Rao, Vijaya Bhaskara; Vemuri, Venkata Deepthi; Gowri, Gollu; Swathi, Nalla; Sasikala, Allam (Indian Journal of Pharmaceutical Education and Research, 2022)
Background: Neuroprotection is one of considerable interest in search of novel therapies to improve ischemic brain damage in the present scenario. The objective of the present investigation is to study the actions of Talinum triangulare in cerebral ischemia/reperfusion induced oxidative stress in Wistar rats and in-vitro antioxidant actions. Methods: Four different groups of adult Wistar rats are selected for study where group III and group IV are treated for 15 days with TTE (200mg/kg, 400mg/kg) earlier to ischemia, on 16th day rats are dissected through global cerebral ischemia by occlusion of unilateral common carotid artery, prior to the dissection animals are sedated with thiopentone and after ischemia induction that 30 min reperfusion was followed. Following the ischemic injury various parameters such as infarct size, SOD, MDA, CAT and GSH levels were assessed after 48hr of reperfusion. Results: Phytochemical screening of TTE indicated the presence of alkaloids, flavonoids, glycosides, carbohydrates, saponins, tannins and resins. TTE also showed a significant in-vitro antioxidant activity. Pre-treatment of TTE for 15 days prior to the ischemic-reperfusion, the results reported a huge reduction in reduction in infarct size, MDA levels and significant increase in SOD, CAT and GSH levels compared to ischemic control rats which was statistically significant. Conclusion: The present study showed that hydroalcoholic extract of TTE leaves showed a significant in-vitro and in-vivo antioxidant activity. The present investigation reported that Talinum triangulare leaves extract showed dose dependant cerebroprotective effect with the selected dose of TTE 200 mg/kg and 400 mg/kg.
Keywords: Talinum triangulare; Cerebral ischemia reperfusion; Oxidative stress; Cerebroprotection; Antioxidant acivity